Retinal Nerve Fiber Layer Decrease during Glycemic Control in Type 2 Diabetes - Masahiko Sugimoto; Mikio Sasoh; Masashi Ido; Chisato Narushima; Yukitaka Uji (Journal of Ophthalmology)
Purpose. To assess an effect of glycemic control on retinal nerve fiber layer (RNFL) in type 2 diabetes mellitus. Methods. Thirty-eight eyes of 38 patients with type 2 diabetes undergoing blood glucose regulation were enrolled. All patients were examined at (1) initial visit, (2) 1 month, (3) 2 months, and (4) 4-month after the initial examination. On each occasion, glycosylated hemoglobin (HbA1c) levels and optical coherence tomography (OCT) scanning for RNFL thickness were evaluated. 360 degree circular OCT scans with a diameter of 3.4 mm centered on the optic disc were performed. Results. Significant RNFL decrease was seen in the superior area between initial and 4 months examination (𝑃=.043). The relationship between the changes in HbA1c and the changes in RNFL thickness was observed in superior, temporal, and inferior area (𝑃<.05) at 4 months. Conclusions. This study suggests that the glycemic control affects RNFL within 4 months.